Blooming phenology and fertility of sour cherry cultivars selected in Hungary - Nyéki, J.; Szabó, T.; Szabó, Z. (International Journal of Horticultural Science, 2002)
Experiments were conducted during the period between 1972 and 2002 at three sites in Hungary. At Érd 97, Helvetia 10, and Újfehértó, 3 cultivars were studied in variety collections. Observations were made on the blooming phenology (start, main time, end and length of the bloom period), on the blooming dynamics (the rate of the open flowers counted every day), on the receptivity of sexual organs, on the fruit set following self- and open-pollination and on the effect of association of varieties in the orchards (choice, rate and placement of pollinisers).Based on the results the rate of the overlap of the blooming times were calculated and varieties were assigned into five bloom time groups according to their main bloom. Self-fertility conditioned by natural self pollination was studied and good pollinisers were chosen (sweet, sour and duke cherry varieties) for the self-sterile and partially self-fertile varieties.The necessity of bee pollination was proved by different pollination methods: natural self-pollination, artificial self-pollination, open pollination. Summary: Experiments were conducted during the period between 1972 and 2002 at three sites in Hungary. At Érd 97, Helvetia 10, and Újfehértó, 3 cultivars were studied in variety collections. Observations were made on the flowering phenology (start, main time, end and length of the bloom period), on the flowering dynamics (the rate of the open flowers counted every day), on the receptivity of sexual organs, on the fruit set following self- and open-pollination and on the effect of association of varieties in the orchards (choice, rate and placement of pollinisers).